Pemberian Diet Diabetes Melitus Nefropati pada Pasien Hiperglikemia Diabetes Melitus Tipe 2 Non Obesitas dengan Anemia Suspect Hepatitis Akut: Sebuah Laporan Kasus - Haq, Nida'ul; Nadhiroh, Siti Rahayu (Media Gizi Kesmas, 2024)
Background: As many as 40% of people with diabetes mellitus type 2 have complications in the kidneys called diabetes mellitus nephropathy. Diabetes mellitus nephropathy is a degenerative disorder in the kidney vascular system that is associated with a disorder of sugar intolerance or carbohydrate metabolism. Anemia can occur in patients with kidney disorders and is exacerbated by acute hepatitis. The Standardized Nutrition Care Process (NCP) to provide proper nutrition to the patient is carried out by administering a 1300 kcal diabetes mellitus nephropathy diet. Objectives: To know the implementation of the Nutrition Care Process by administering a 1300 kcal Diabetes Mellitus Nephropathy diet to patients. Methods: A case study was conducted in March 2021 in patients at Bhayangkara Surabaya Hospital. Sampling has been determined in advance by the hospital nutritionist and internship guide according to the case criteria. The data collection method is carried out with observation and analysis over 3 days in the field of intake, physical/clinical, biochemical, and anthropometry. The researchers also conducted literature studies to supplement the data. Results: Monitoring and evaluation results showed that there were fluctuating changes in laboratory, physical/clinical outcomes, and patient intake. At the patient’s energy intake increased from day to day but macronutrient fulfillment has not reached the target (<80%). Conclusions: The patient's recovery condition was not sufficiently good, from the physical/clinical monitoring results still showed a decrease, and the results of the biochemical examination showed an increase in Hb levels in patients despite still being low, and for three days it was found that patient intake increased despite being insignificant and still not meeting the targeted daily needs.